Simultaneous Detection of Fumonisin 81, Fumonisin B2 , T-2, HT-2 in rice using HPLC-ESI-MS/MS / Nur Atiqah Ahmad Fisal - Ahmad Fisal, Nur Atiqah (2014)
A high performance liquid chromatography - electrospray ionization - tandem mass spectrometry (HPLC-ESI-MS/MS) method is described for simultaneous determination .of fumonisins (FB1 and FB2), T-2 and HT-2 toxin in rice. Mycotoxins were separated by reverse phase liquid chromatography and detected in positive ion modes. The mean recoveries of FB 1, FB2, T-2 and HT-2 from spiked rice sample ranged from 85.25% to 92.16%, whereas the limit of detection (LOO) and limit of quantification (LOQ) are 15 ng/g and 45 ng/g, respectively. The developed method was applied for the determination of selected mycotoxins in 96 rice samples collected from Selangor state, Malaysian. Although almost 15% of rice samples were contaminated with at least one of this mycotoxins, only 14.6 % of rice samples were positive at level greater than the LOO. However, the samples are not exceeding the European regulatory limits.